Alluvial to lacustrine sedimentation in an endorheic basin during the Mio-Pliocene: The Toro Negro Formation, Central Andes of Argentina - Ciccioli, Patricia Lucia (2018)
A 2400 m-thick sedimentary column belonging to the Toro Negro Formation was recorded along the Quebrada del Yeso, Sierra de Los Colorados (Vinchina Basin), La Rioja province, NW Argentina. The Vinchina basin is a good example of a closed basin surrounded by the Precordillera fold and thrust belt to the west and basement-cored blocks to the north, south (Western Sierras Pampeanas) and east (Sierra de Famatina). Seven facies associations (FA) are described and interpreted to represent fluvial, lacustrine and alluvial environments developed in the southern part of the Vinchina basin from the Late Miocene until the earliest Pleistocene. The depositional evolution of the formation was divided in four phases. Phase I (∼7–6.6 Ma) represents sedimentation in medial (FA I) to distal (FA II) parts of a southward directed distributive fluvial system with a retrogradational pattern. During phase II (6.6–6.1Ma), the distributive fluvial system was replaced by a mixed clastic-evaporitic shallow lake (FA III) in a high aggradational basin. In phase III (∼6.1–5 Ma) the eastward progradation of a fluvial system (FA IV) was recorded as a distal clastic wedge. Finally, phase IV (∼5-2.4Ma) records two depositional cycles of proximal clastic wedge progradation of fluvial-dominated piedmonts (FAV, FAVII) from the southwest (Sierra de Umango) and/or the west (Precordillera) with an intervening playa lake (FA VI). Two new U-Pb ages obtained from zircons in volcanic ash layers confirm the Late Miocene age of the lower member of the Toro Negro Formation and permit a tight correlation with the central part of the basin (Quebrada de La Troya section). The sedimentation rate calculated for the dated lacustrine-fluvial interval is higher than the corresponding one in La Troya area suggesting a higher subsidence in the southern part of the basin. During the Late Miocene (∼7-6.6Ma) the ephemeral drainage was controlled by an arid to semiarid climate and initially dissipated mostly internally as terminal fan/distributive fluvial systems descending from the north. A thick lacustrine interval developed in the southern part of the basin between ∼6.6 and 6.1 Ma during a period of high subsidence and closed drainage. Besides, this interval coincides with increased aridity recorded in other basins in the Northwest of Argentina. By ∼6.1 Ma the area started to receive the first coarse-grained sediments heralding the progradation of a clastic wedge from the southwest-west (Sierra de Umango and Precordillera) which fully developed during the rest of the Pliocene to the earliest Pleistocene (∼5–2.4 Ma). The 6.1–2.4 Ma interval records ameliorating climate conditions.